Editorial: saving mothers and babies for the new world - Ahmad Kamar, Azanna; Cheah, Fook-Choe; Ismail, Hamizah; Pejaver, Ranjan; Ellwood, David Alan; Abdullah Mahdy, Zaleha (Frontiers Media S.A., 2023)
First, where or what is the New World? Historically, this refers to the region of the Americas. In this context, the New World is the future of humankind, an ambiguous borderless phenomenon that is informed and built upon from lessons of its past and from stories of triumph and regrets; of innovations, experiences of the pandemic, economic successes, and failures; of those unwanted wars; and of great science. The New World we envision emphasizes the quintessential of actions to ensure human survivability, by prioritizing equitable care to mothers and babies regardless of their region. Positive outcomes for mothers and babies can only be achieved by ensuring that healthcare professionals are knowledgeable, holistic, ethical, and safe and that effective execution of ethically robust healthcare policies and guidelines for equitable perinatal healthcare is adequately supported. These aims need to be at the forefront of policies of governments across all countries in the New World despite all setbacks. With this in mind, the research topic Saving Mothers and Babies for the New World accepted 16 diverse full-length articles and collected abstracts presented at the 21st Federation of Asia Oceania Perinatal Societies (FAOPS) Congress that provided a wealth of information and science that can help carve future research and inform policies.